MAKANAN HIGIENIS DAN BERGIZI DALAM PERSPEKTIF AGAMA ISLAM - Munasib, Munasib; Sa’dudin, Ihsan (Jurnal Tawadhu, 2019)
Material content of Islamic Education at the University of Health is not only related to pure Islamic material. But ideally it is correlated with facultative-based material and study programs.Food studies in the Nutrition Science Study Program will always be interesting and developing, one of the focuses of the study is about food safety and halalness. Many studies have examined food security using the food science and health sciences approaches, but there are still few studies that discuss food halalness. Therefore an interdisciplinary approach is needed, namely integrating Islamic science approaches (Islamic Education) with health sciences. The purpose of this study is to find a picture of the concept of hygienic and nutritious food in the perspective of Islam.